ACCELERATION ANALYSIS USING THE CRASHING METHOD ON THE PROBOLINGGO-BANYUWANGI TOLL ROAD PACKAGE 1 PROJECT - Sandy Lovely Madina; Fauzi Akbar Rahmawan (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2025)
Probolinggo-Banyuwangi Toll Road Package 1 is one of the government projects to complete the Trans Java Toll Road. Based on the plant schedule, it must be finished in 2024, but because of many factors, this project has some delays. Because of those problems, this research aims to find an effective approach to accelerate based on time and cost. One of the effective ways to solve this problem is by using the crashing method, which only accelerates the critical activity using the Microsoft Project. After determining the critical path, five scenarios will be created with different activity options, each scenario targeted to accelerate 4 weeks or 1 month. All scenarios will be compared to find the most effective scenario based on the cost. The analysis results are as follows: 1) Scenario 1 requires an acceleration cost of IDR 6.548.955.840,05; 2) Scenario 2 requires an acceleration cost of IDR 6.549.764.555,46; 3) Scenario 3 requires an acceleration cost of IDR 6.895.340.767,67; 4) Scenario 4 requires an acceleration cost of IDR 7.368.457.309,22; 5) Scenario 5 requires an acceleration cost of IDR 6.371.649.065,18. From those five scenarios, the most effective is scenario 5, which only requires IDR 6.371.649.065,18, and the activity that has been accelerated is Common Borrow Material; U Channel Type DS-6A; U Ditch 1×1,5; U Channel Type DS-8A; Rigid Pavement Concrete; Structural Concrete Class C-1; Vehicle Guardrail Type A; and Concrete Berries Type B, allowing the project finish earlier by 4 weeks or 1 month.